Design and Implementation of Three-Level DC-DC Converter with Golden Section Search Based MPPT for the Photovoltaic Applications. (12th February 2015) - Balakishan, Chouki; Sandeep, N.; Aware, M. V.
Abstract : In many photovoltaic (PV) energy conversion systems, nonisolated DC-DC converters with high voltage gain are desired. The PV exhibits a nonlinear power characteristic which greatly depends on the environmental conditions. Hence in order to draw maximum available power various algorithms are used with PV voltage/current or both as an input for the maximum power point tracking (MPPT) controller. In this paper, golden section search (GSS) based MPPT control and its application with three-level DC-DC boost converter for MPPT are demonstrated. The three-level boost converter provides the high voltage transfer which enables the high power PV system to work with low size inductors with high efficiency. The balancing of the voltage across the two capacitors of the converter and MPPT is achieved using a simple duty cycle based voltage controller. Detailed simulation of three-level DC-DC converter topology with GSS algorithm is carried out in MATLAB/SIMULINK platform. The validation of the proposed system is done by the experiments carried out on hardware prototype of 100 W converter with low cost AT'mega328 controller as a core controller. From the results, the proposed system suits as one of the solutions for PV based generation system and the experimental results show high performance, such as a conversion efficiency of 94%.